2002
DOI: 10.1046/j.1365-2516.2002.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolving perspectives in product safety for haemophilia

Abstract: The past decade has seen a consolidation of the safety measures built into the manufacture of coagulation factor concentrates for people with haemophilia. The scientific developments of the 1980s have been fully reflected in the manufacturing principles and the regulatory control of concentrate production, so that the safety of concentrate therapy now exceeds the safety of normal blood transfusion. A clear understanding of the epidemiology of the transfusion-transmitted viruses allows the selection of donors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
0
17
0
3
Order By: Relevance
“…In contrast a cohort that evaluated 62 patients treated with the same brand of high-purity plasma-derived FVIII (pFVIII) containing Von Willebrand factor (VWF) and 86 patients treated with full-length rFVIII concluded that the risk of inhibitor development was higher in patients treated with rFVIII than in patients treated with pFVIII, regardless of other risk factors (F8 genotype; non-white origin; history of inhibitors in patients with a family history of haemophilia; age at first FVIII infusion). The adjusted relative risk (RR) for inhibitor development with rFVIII versus pFVIII was 2.4 [36,37].…”
Section: Summary Of Findings On Treatmentmentioning
confidence: 99%
“…In contrast a cohort that evaluated 62 patients treated with the same brand of high-purity plasma-derived FVIII (pFVIII) containing Von Willebrand factor (VWF) and 86 patients treated with full-length rFVIII concluded that the risk of inhibitor development was higher in patients treated with rFVIII than in patients treated with pFVIII, regardless of other risk factors (F8 genotype; non-white origin; history of inhibitors in patients with a family history of haemophilia; age at first FVIII infusion). The adjusted relative risk (RR) for inhibitor development with rFVIII versus pFVIII was 2.4 [36,37].…”
Section: Summary Of Findings On Treatmentmentioning
confidence: 99%
“…A considerable percentage of cell lines was established before viral contaminations had been routinely assayed or even before those viruses had been discovered. Additionally, the risk of emerging pathogens has to be kept under constant review [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Although most inhibitors are either transient or resolve with immune tolerance therapy, ∼ 15% of FVIII-deficient patients and 3% of FIX-deficient patients have persistent clinically significant inhibitors, which result in severe morbidity [13,14]. Finally, although the risk of transmission of infectious agents has been largely overcome by the development of recombinant factor products, there still exists at least the theoretical risk of infection from prions and unforeseen infectious agents perhaps from the use of mammalian cells in the production of factor concentrates [15]. Future treatment for haemophilia revolves around improving on these negative aspects of therapy.…”
Section: Medical Needmentioning
confidence: 99%